A Kinase Anchoring Protein 9 Is a Novel Myosin VI Binding Partner That Links Myosin VI with the PKA Pathway in Myogenic Cells. (16th April 2015) - Karolczak, Justyna; Sobczak, Magdalena; Skowronek, Krzysztof; Rędowicz, Maria Jolanta
Abstract : Myosin VI (MVI) is a unique motor protein moving towards the minus end of actin filaments unlike other known myosins. Its important role has recently been postulated for striated muscle and myogenic cells. Since MVI functions through interactions of C-terminal globular tail (GT) domain with tissue specific partners, we performed a search for MVI partners in myoblasts and myotubes using affinity chromatography with GST-tagged MVI-GT domain as a bait. A kinase anchoring protein 9 (AKAP9), a regulator of PKA activity, was identified by means of mass spectrometry as a possible MVI interacting partner both in undifferentiated and differentiating myoblasts and in myotubes. Coimmunoprecipitation and proximity ligation assay confirmed that both proteins could interact. MVI and AKAP9 colocalized at Rab5 containing early endosomes. Similarly to MVI, the amount of AKAP9 decreased during myoblast differentiation. However, in MVI-depleted cells, both cAMP and PKA levels were increased and a change in the MVI motor-dependent AKAP9 distribution was observed. Moreover, we found that PKA phosphorylated MVI-GT domain, thus implying functional relevance of MVI-AKAP9 interaction. We postulate that this novel interaction linking MVI with the PKA pathway could be important for targeting AKAP9-PKA complex within cells and/or providing PKA to phosphorylate MVI tail domain.